ANALISIS PENGARUH MOTIVASI TERHADAP PRESTASI KERJA KARYAWAN PADA PT. MAKASSAR RAYA MOTOR - Arniati Arniati (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
Which wish reached performed of this research to analyse the influence motivate the job to labour capacity employees at PT. Makassar Raya Motor Makassar, and also to analyse the relation of between motivation work with the labour capacity of employees at PT. Makassar Raya Motor Makassar. To solve the the problems hence analysis method used by : analysis of regresi and correlation and also analyse the validity and reliabilitas for instrument research. Result of analysis conducted indicate that there are influence of between motivation to labour capacity of employees at PT. Makassar Raya Motor Makassar, this matter is knowable through/ passing analysis regresi of between motivation with the labour capacity employees, obtained by equation regresi that is Y = 0,957 + 0,730 ( X), indicating that with the existence of the make-up of job motivation of diiikuti with the make-up of labour capacity employees of equal to 0,730 and with the value prob < 0,05 can be said that by a motivation work to have an effect on by signifikan to make-up of labour capacity employees.